A referência anafórica por encapsulamento: gramática e discurso - Pacheco, Lucivânia Marques [UNESP] (2014)
The goal of this work is to analyze the functioning of anaphoric encapsulation, taking into account the instances in which this phenomenon takes place. Based on the postulates of Functional Discourse Grammar of Hengeveld and Mackenzie (2008), this study aims to show that there is an instance of referencing that is marked in grammar and another component - the identification of the textual portion of an anaphoric encapsulation - that is solved in the Contextual Component, as postulated by Hengeveld and Mackenzie (Unpublished). By means of a dialogue with the works of Connlly (2007), Cornish (2009) and Stassi-Sé (2012), this study highlights the need for a redefinition of the Contextual Component. This proposal is confirmed by the analysis of reference encapsulation occurrences found in personal opinion texts circulating in two weekly magazines (Veja and Caros Amigos Online). The analysis of those events suggests that the phenomenon of anaphoric referencing through encapsulation articulates properties of socio-cognitive, discursive, semantic and morphosyntactic nature and that some regularities of its functioning are explained through the levels and layers of the FDG